Feasibility and effectiveness of second-line chemotherapy with mitomycin C in patients with advanced penile cancer - Draeger, Desiree Louise; Hakenberg, Oliver W. (Frontiers in Urology, 2024)
Background Triple-drug cisplatin- and taxane-based chemotherapy is the standard treatment for metastatic penile squamous cell cancer (PeSCC), with a moderate response rate of 30% to 38%. Relapse after first-line chemotherapy has a poor prognosis and there is no established second-line treatment. Mitomycin C (MMC) is used as an effective chemotherapy in squamous cell carcinoma of other localities. We therefore used MMC as a single agent for the second-line treatment for patients with advanced PeSCC. Methods Nine patients [median age 63 years (range 31 years–81 years)], who, after inguinal and pelvic lymphadenectomy and progression after first-line chemotherapy, received second-line treatment with 20 mg of MMC administered intravenously and weekly, were included in this study. The median number of cycles of MMC was 6 (range 2–12 cycles) and the median cumulative dose was 120 mg absolute (range 40 mg absolute–240 mg absolute). The patients’ toxicity and treatment responses were evaluated, with the latter evaluated using 18F-FDG-PET/CT. Results Common Terminology Criteria for Adverse Events (CTCAE) grades 3 or 4 thrombocytopenia and grades 2 or 3 leukopenia occurred in all patients, as did anemia. In seven patients, the application interval had to be extended due to thrombocytopenia. Stable disease was achieved in two patients, and all others progressed under treatment. Seven patients died of the disease, with most patients dying 6 months after starting MMC therapy. Of the two patients who responded with disease stabilization, one died of progressive disease 14 months after MMC treatment. The other responding patient has been stable for over 1 year and is still receiving treatment, which he tolerates well, and has a good quality of life. Conclusion MMC has only moderate efficacy as a second-line treatment in patients with metastatic PeSCC. With MMC treatment, hematological toxicity is marked.